Employee Professional Improvement Model Civil State in Resource Staff Work Units State Police Human Power Republic of Indonesia - Yudianto Adhi Nugroho; Nurliah Nurdin; Hamka Hamka (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The purpose of this study was to analyze the factors or variables that most dominantly influenced the increase in civil servant professionalism and to apply the development of a strategic model to increase the professionalism of civil servants in the National Police's SSDM satker by using the concept of Strategic Human Resource Management theory from Noe, et al. The method used is the mixed method methodology. Data collection was carried out through questionnaires and interviews as well as document review. The results showed (1) the factors that most dominantly influenced the increase in the professionalism of civil servants in the National Police's SSDM satker were aspects of job design, selection, training and development, compensation, performance management and employee relations which had not been carried out optimally.